The political economy and civil service reform - Briones, Leonor M. (2005)
The Philippines is likely to have the best civil service only if legal reforms passed to improve/enhance the system are seriously implemented. Despite reform initiatives, the bureaucracy remains ineffective and damaged. Public administrations scholars emphasize that civil service reforms can only be achieved and strengthened with sustainable economic growth, and political maturity and stability. Heightened and publicized movement on civil service reforms, urgent ratification of the Civil Service Code, reasonable and standardized salaries of professionals doing similar jobs, and high regard for trustworthy and outstanding civil servants will certainly contribute to advance reforms in the civil service. Ultimately, the active participation of all the different sectors in society is vital to revolutionize the government system.
Keywords: Administrative Code of 1987; Economics; Redemocratization; Government agency reorganization